Which people are willing to maintain their subordinated position? Social dominance orientation as antecedent to compliance to harsh power tactics in a higher education setting. (1st December 2019) - Tesi, Alessio; Aiello, Antonio; Morselli, Davide; Giannetti, Enrichetta; Pierro, Antonio; Pratto, Felicia
Abstract: Social dominance theory (SDT; Sidanius & Pratto, 1999) hypothesizes that members of subordinate groups who are higher on social dominance orientation (SDO; desire for maintaining status hierarchies) coordinate with dominant ones in maintaining asymmetrical relationships. The present research tests this hypothesis in a higher education setting by examining whether SDO serves as an antecedent to subordinates' compliance with harsh power tactics. A longitudinal study asked students ( N = 91) to imagine themselves in a subordinated condition doing specific tasks in which they were supervised by a professor. Respondents' SDO and compliance to harsh tactics were measured at two different times. A cross-lagged path analysis, using Bayesian estimation, supported the hypotheses. Students' SDO measured at time 1 predicted their compliance to harsh power tactics measured at time 2, controlling for their initial levels of compliance to harsh power tactics. There was no evidence for the converse; students' compliance to harsh power tactics at time 1 did not predict SDO measured at time 2 taking into account the initial levels of SDO.